The Effect of Competence, Information Technology and Complaint Handling on Customer Satisfaction Intervening Service Quality - PURNOMO, Edy; NGALIMAN, Ngaliman; YANTI , Sri (PT Keberlanjutan Strategis Indonesia, 2025)
The public satisfaction index value for the services of the Kijang Class III Port Authority and Harbormaster Office, Riau Islands, is in the poor category, due to customer satisfaction issues related to service quality, employee competence, information technology utilization, and complaint handling. This mixed-methods study aims to examine the relationship between competence, information technology utilization, and complaint handling on customer satisfaction in the intervening period. Service quality. It was concluded that competence, complaint handling, and service quality had a significant positive effect on customer satisfaction. Furthermore, competence and complaint handling had a significant positive effect on service quality. Then, the use of information technology had a positive but insignificant effect on customer satisfaction. Furthermore, complaint handling did not have a significant positive effect on service quality. Then, service quality was able to intervene in the influence of competence and information technology utilization in a significant positive way on customer satisfaction, but was unable to intervene in the influence of complaint handling on customer satisfaction. It is recommended to the leadership elements of the agency, among others, to optimize the condition of the technology infrastructure and create a training program to improve the basic skills of officers in using technology in communicating information to customers and prioritize the main targets of service performance to be oriented towards optimizing complaint handling.